The transformative impact of extracellular vesicles on developing sperm - Michael P Rimmer; Christopher D Gregory; Rod T Mitchell (Bioscientifica, 2021)
Objective: To review the role of extracellular vesicles (EVs) released from the male reproductive tract and their impact on developing sperm. We discuss how sperm exiting the seminiferous tubules, although developmentally mature, require further modification. Acquisition of various functions including increased motility, transfer of cargoes and ability to undertake the acrosome reaction is mediated through the interaction between sperm and EVs. Methods: A review of the literature identified that EVs are released from different portions of the male reproductive tract, notably the epididymis and prostate. These EVs interact with sperm as they pass from the seminiferous tubules to the epididymis and vas deferens prior to ejaculation. Results: EVs are small lipid-bound particles carrying bespoke RNA, protein and lipid cargoes. These cargoes are loaded based on the state of the parent cell and are used to communicate with recipient cells. In sperm, these cargoes are essential for post-testicular modification. Conclusions: Interactions between developing sperm and EVs are important for the subsequent function of sperm. Prior to ejaculation, these interactions confer important changes for the post-testicular modification and development of sperm. Little is known about the interaction between EVs from the testes and the spermatogonial stem cell niche or developing sperm within the seminiferous tubules. However, the numerous roles of EVs in the post-testicular modification of sperm have led many to suspect that they may also play important roles in developing sperm within the testes.